Evaluation Of Prior Learning Recognition (RPL) Program In Higher Education - Irdalisa Irdalisa; Benny Hendriana; Isnaini Handayani; Arum Fatayan; Isa Faqihuddin Hanif; Tri Wintolo Apoko (Jurnal Mamangan, 2025)
The purpose of this study was to evaluate how the Recognition of Prior Learning (RPL) program is implemented in Higher Education. The learning process in Indonesia is currently no longer limited to the classroom or formal academic environment. The acquisition of knowledge and skills obtained for the community can be through work experience, training, and non-formal activities. The Recognition of Prior Learning (RPL) program is designed to recognize and validate knowledge and skills obtained outside of formal education, by providing academic credits equivalent to the results of learning in the classroom. RPL serves as an important bridge for students to utilize their experiences and accelerate the completion of studies in higher education. This research method is descriptive-quantitative with 73 students as research subjects. The results showed that this RPL program received a positive response and became the choice of students in continuing their studies. Regarding the stages of the RPL program learning activities, 66.7% of newly registered students strongly agreed and 33.3% agreed that the learning activities encouraged students' curiosity because the material studied was linear with their field of work. Regarding the benefits of the RPL program, 84.2% of RPL students strongly agreed and 15.8% agreed that during the RPL program they gained a lot of new experiences and knowledge that could be implemented in their work. This RPL program contributes to workers to gain access to education, improve competency, obtain a bachelor's degree and support career plans. Thus, the implementation of RPL must be guaranteed in quality so that graduates have standardized graduate achievement quality